2023
DOI: 10.1371/journal.pone.0279893
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum periostin levels and the severity of arsenic-induced skin lesions

Abstract: Arsenic is a potent environmental toxicant and human carcinogen. Skin lesions are the most common manifestations of chronic exposure to arsenic. Advanced-stage skin lesions, particularly hyperkeratosis have been recognized as precancerous diseases. However, the underlying mechanism of arsenic-induced skin lesions remains unknown. Periostin, a matricellular protein, is implicated in the pathogenesis of many forms of skin lesions. The objective of this study was to examine whether periostin is associated with ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…In systemic sclerosis, POSTN promotes and intensifies skin fibrosis. In AD, POSTN exacerbates tissue remodeling, leading to the development of hyperkeratotic skin lesions with distorted architecture [3,7,8]. AD and psoriasis are dermatoses characterized by epidermal hyperplasia, but the immune response in each of these diseases occurs differently.…”
Section: Introductionmentioning
confidence: 99%
“…In systemic sclerosis, POSTN promotes and intensifies skin fibrosis. In AD, POSTN exacerbates tissue remodeling, leading to the development of hyperkeratotic skin lesions with distorted architecture [3,7,8]. AD and psoriasis are dermatoses characterized by epidermal hyperplasia, but the immune response in each of these diseases occurs differently.…”
Section: Introductionmentioning
confidence: 99%
“…The participants were from high-arsenic exposure villages in the region that included Marua in the Jessore district; Dutpatila, Jajri, Vultie, and Kestopur in the Chuadanga district; Khemirdia (Bheramara) in the Kushtia district; and Kazirpara in the Rajshahi district. During our visit to these villages, we found many residents with arsenical skin lesions (melanosis, leucomelanosis, keratosis, and hyperkeratosis), 39 the hallmark features of prolonged exposure to high concentrations of arsenic. The prevalence of arsenical skin lesions suggested that the residents living in those regions were exposed to high levels of arsenic.…”
Section: Methodsmentioning
confidence: 98%
“…Pigmentary changes are considered the earliest dermatological manifestations and may act as an early marker of carcinogenicity. 18 The public should pay close attention to arsenic-induced pigmentary changes and explore the risk factors for susceptibility.…”
Section: Introductionmentioning
confidence: 99%